A participação do governo estadual no amadurecimento da esfera pública: um estudo de caso em Pernambuco. - Diniz, Lucio Gustavo de Paiva Genu (2010)
This present research shows an analysis of how the State interferes on the public sphere of six areas in the Metropolitan Area of Recife. By implanting a team of actions that involved nine state bureaus, the State Government established a interlocution methodology with the leaders at the assisted communities. By studying this methodology, and by using the structure defined by Jürgen Habermas, that offers the State a similar function as the mass communications, such as to inform society, and a debate between contemporary theories of public administration with a managerial view and the social public administration, added with a brief description of the evolution of popular participation in Brazil and in Pernambuco since the early 1930s, the dissertation goes to the description of socio-economic information of the included areas and, following, by semi-structured interviews taken place on a sample of 53 communities leaderships, it ends the case study by claiming that, although it is fulfilling its responsibility to inform the governmental actions to the public sphere, this program still doesn’t correspond to its expectation to promote improvement on local public sphere.